2016
DOI: 10.1136/annrheumdis-2016-eular.2516
|View full text |Cite
|
Sign up to set email alerts
|

AB0699 Enthesitis and Sacroiliitis Prevalence Determined by Doppler Ultrasonography and Magnetic Resonance Imaging in Patients with Inflammatory Bowel Disease

Abstract: BackgroundPatients with inflammatory bowel disease (IBD): Crohn disease (CD) and ulcerative colitis (UC) can develop extraintestinal manifestations and ones of the most important are musculoskeletal affections. In published studies, the prevalence of Spondyloarthritis (SpA) stands from 10 to 20% but with a wide range of variation. These differences are related to the methods used for its determination.Objectives1) To determine the prevalence of sacroiliitis with X-ray or magnetic resonance imaging (MRI) and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In the four studies using MRI, the prevalence of sacroiliitis ranged from 20.0% to 38.6%. 41 , 45 , 50 , 51 The prevalence of sacroiliitis in the four studies using MRE ranged from 15.4% to 28.9%. 39 , 42 , 49 , 53 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the four studies using MRI, the prevalence of sacroiliitis ranged from 20.0% to 38.6%. 41 , 45 , 50 , 51 The prevalence of sacroiliitis in the four studies using MRE ranged from 15.4% to 28.9%. 39 , 42 , 49 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…A higher prevalence of sacroiliitis was seen in the studies using dedicated imaging of the SIJs, with four of the six SIJ imaging studies observing this (see Figures 2 and 3 ). 30 , 45 , 47 , 51 All of the studies utilising SIJ CT imaging observed a higher prevalence compared with only half of the studies using SIJ MR imaging. In contrast, only one study using IBD imaging was found to observe a higher prevalence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations